Fronting the Return of Foreign Terrorist Fighters: the Rise and Fall of ASEAN Border Cooperation to Combat Non-Traditional Threats - Suryadi, Muhammad; Timur, Fauzia Gustarina Cempaka (Jurnal Hubungan Internasional, 2018)
This paper argues that bilateral arrangements among ASEAN countries are no longer enough to address the convergence of non-traditional threats, primarily due to porous borders in Southeast Asia region. Hence, fighting terrorism by securing maritime border through ASEAN border cooperation is seen as a useful measure to respond the issue. This paper aims to observe non-traditional threat posed from the maritime boundary, specifically from Indonesia, Malaysia, and the Philippines border which each of the government has agreed on Defense and Security Agreement Framework in the past few years. The FTF returnees and the existential threat of terrorism in each ASEAN countries have eventually carried a new agenda for ASEAN countries in securing the border. This paper then analyses the result of the Trilateral Meeting that depicts the commitment of these countries in tackling FTF as the growing security challenges in the region. This paper also considers the effectiveness of the Trilateral Agreement in combating non-traditional threats including terrorism.